ISLAMIC DISRUPTION: How Digital Platform Changes Religious Pattern of Muslim Society in Contemporary Indonesia - Zainuddin Syarif; Abd Hannan (IAIN Ponorogo, 2022)
This study discusses the phenomenon of Islamic disruption among contemporary Muslims in Indonesia. There are three research questions discussed in this study; How is the existence of Muslim netizens in Indonesia today? What are the religious dynamics that occur among Muslim netizens in Indonesia? How does the disruption of Islam affect their religious patterns and behavior? By conducting an in-depth analysis based on the perspective of postmodern sociological theory, this study found three findings; First, contemporary Indonesian Muslims are Muslim netizens who have a high dependence on technology and information media with digital platforms. Second, the Islamic disruptions among native Muslims occur in two aspects, namely the aspect of worship marked by a shift in religious behavior from traditional rituals to modern rituals. Next is the education aspect, shifting the Muslim netizen's religious learning tradition which is no longer centered in the conventional space, but shifts to a digital-based virtual space. Third, religious disruption affects the religious culture of Muslim netizens through three elements; speed, surprise, and finally a sudden shift.